DETERMINANTS OF MOTHERS’ PARTICIPATION IN ANTENATAL CLASSES - Sutopo Patriajati; Ayun Sriatmi (Universitas Airlangga, 2019)
Background: As a form of health promotion, Antenatal Education (AE) class is expected to improve the knowledge, attitudes, and practices of mothers facing their pregnancy. Access to antenatal classes for mothers has not been optimal because of the low level of participation. Not all mothers are willing to join antenatal classes for various reasons.Aim: This study aimed at analyzing the determinant factors that influence the mother’s participation in antenatal classes.Method: This study was a quantitative study with a cross-sectional approach. The population was all pregnant women in Semarang City with 140 pregnant mothers as samples from 3 Primary Healthcare Centers including Rowosari, Purwoyoso, and Gayamsari which were selected by using a purposive sampling technique. Data were collected through an interview using a structured questionnaire.Results: The findings showed that only 54.3% of mothers attended the antenatal classes. Knowledge, support from health personnel, facilities, and infrastructure, as well as a history of illness and pregnancy, affect mothers’ participation in antenatal classes where the support of health workers had the most dominant influence (OR 5.394). The overall influence was 39.2%.Conclusion: The low mothers’ participation in antenatal classes was influenced by the lack of knowledge and support, inadequate facilities as well as the low health status of mothers. Further socialization and engagement across related sectors with strong networking are needed to solve this problem.Keywords: antenatal education, participation, primary healthcare center.